O Eu e o Outro na sala de aula ocultando e revelando máscaras - Zamperetti, Maristani Polidori (2007)
The teacher-artist-researcher s personal experiences and the artistic process shared with primary school students constitute the initial motivation of this project work. Throughout a research-action in the field of teaching arts, students were oriented to produce self-portraits, portraits and tridimensional masks with drawings, paintings and gluing. Combined with personal files and narrative texts by the pupils, the artistic production was studied as elements of research. Class observation, field record notes and registered conversations were also as data for the research-action. The experience was rich in questioning and multiple in artistic manifestations, addressing the student himself and its daily life. The students revealed personal and collective stories of life and their experienced communicational process made the recuperation of the students relationship forms with their expressivity possible. The visual forms that appeared in this work came from their own interests and personal likes as well as mediatic influence, class and family inter-relationships, juvenile conflicts and imaginations and the need to pass their own limitations through fantasy and inventivity. The communicational-reflexive teaching provided the teacher-researcher moments of interlocution with the student s task, questioning, finding and learning of both parts in the creative process of inter-relations spaces.